The Impact of Food Price Shock on Heterogenous Credit Constrained Firms - Pavel Ciaian; d'Artis Kancs (Economics and Econometrics Research Institute (EERI), 2008)
This paper analyses how rising agricultural prices affect heterogenous farm production and access to inputs under credit market imperfections in the CEE transition countries. Using the FADN farm level panel data, which contains 37416 observations for 2004 and 2005, we estimate a farm credit constraint equation and find that small individual farms (IF) are more credit constrained that large corporate farms (CF). Using the estimated parameters we simulate the effect of rising input and output prices on production and input use of IF and CF farms. Our results suggest that in the presence of credit market imperfections, the relatively less credit constrained CF tend to benefit more from higher output prices than IF. Given that farms in transition and developing countries are more credit constrained than farms in developed market economies, raising food prices may actually reduce their profits and income compared to the latter. Hence, not only consumers but also agricultural producers in the developing world may loose from the increasing food prices.
Keywords: Q11; Q12; P23; 330; Credit constraint; food prices; firm level heterogeneity